Advanced Materials for Emerging Water Pollutant Removal - Pei Sean, Goh; Devagi, Kanakaraju; Anwar, Iqbal; Ahmad Fauzi, Ismail (Royal Society of Chemistry, 2024)
Water scarcity is an increasing issue on every continent. Along with climate change, the global issue is escalated by urbanization, population growth, and pollution. According to the World Bank report, 80% of wastewater enters water bodies without being adequately treated. The release of vast amounts of industrial and domestic wastewater results in the pollution of the water environment and ecosystem. Proper treatment of these wastewaters allows their reutilization for many purposes and applications including industrial processes and irrigation. Advanced materials are known to be promising tools to alleviate the impacts of these issues. In the last decade, tremendous efforts have been made to progress in the field of synthesis and application of advanced materials especially for use in environmental remediation. Advanced materials including nanomaterials and biomaterials can be used to remove pollutants from water and air. A wide range of advanced materials can be prepared through affordable, energy-efficient approaches. They can also be easily retrofitted in existing wastewater or air filtration systems.